‘A Manifesto for Decolonial Subversions’ - Hirmer, Monika (Decolonial Subversions, 2022)

‘Devī Needs those Rituals!’ Ontological Considerations on Ritual Transformations in a Contemporary South Indian Śrīvidyā Tradition - Hirmer, Monika (Religions of South Asia, 2020)
Negotiations between continuity and discontinuity have characterized Śrīvidyā traditions for centuries; these are primarily studied through texts or the juxtaposition of textual prescriptions with observed practices, leaving the process of how Śrīvidyā practitioners negotiate esoteric and orthodox tendencies unexplored. Building on extensive fieldwork among practitioners of a contemporary South Indian Śrīvidyā tradition, I present the dynamics animating such transformations. Focusing on kalāvāhana, one of the tradition’s central rituals aimed at identifying with Devī, I trace the underlying forces that gradually replace its most esoteric aspects (centred around the body and pleasure) with conventional worship (external or meditative practices), refashioning the tradition as part of mainstream Śāktism. While some practitioners conform to the new canon, others, for whom the changes diminish ritual efficacy, secretly continue embodied practices. Through a Foucauldian archaeologico-genealogical analysis, I investigate which regimes of truth and ontological coordinates allow the ritual to change, and which diminish its efficacy. While at first negotiations between continuity and discontinuity appear driven by socio-political motives, ultimately they are governed and legitimized by fundamentally diverging modes of being. A pre-objectified worldview demands embodied experiences (including unconventional practices invoking pleasure) while a dualistic framework endorses representational practices (such as meditation and idol-worship).
Created from Fastlane, Scopus look-up
Keywords: Embodiment; Goddess worship; Ontology; Ritual transformation; Tantra; Śrīvidyā

‘Let us now invoke the three celestial lights of Fire, Sun and Moon into ourselves’ - Hirmer, Monika (Tantra, Magic, and Vernacular Religions in Monsoon Asia, 2022)
This chapter tries to depart from the positivistic existential outlook cast by Western scholarship on the ‘magical’ rituals carried out by South Indian Śrīvidyā practitioners to cultivate oneness with goddess Tripurasundarī. Hirmer explores the ontological coordinates that accommodate this oneness cogently and unambiguously and proposes a radical re-evaluation of the concept of ‘beingness’ as conceived by a modern scientific framework, revealing an emic understanding where bodies expanding into subtle realms and actions partaking in cosmic designs respond to ontological coordinates informed by transcendence. The ontological dislocation she advocates, where identities and practices deviating from a positivistic framework need no longer be confined to the domain of ‘magic’ but can be appreciated in their ontological primacy and epistemic legitimacy, invites novel, decolonial, modes of approaching the Śrīvidyā tradition and Tantric traditions generally.<br

‘Looking for the Indian Woman’s Identity: Discrepancies and Power Imbalances Across Theory and Popular Culture’ - Hirmer, Monika; et al. (SOAS Journal of Postgraduate Research, 2016)

‘Reflections on Salient Features in Clifford Geertz’s Interpretive Approach to Cultural Analysis’ - Hirmer, Monika (SATIS Interdisciplinary Postgraduate Journal of Goodenough College, 2019)

Taking Cringe Pop Seriously - Hirmer, Monika (Economic and Political Weekly, 2018)

The Art of Telangana Women and the Crafting of the Decolonial Subject. From Dialectics of “Othering” to Expressions of Radical Alterity - Hirmer, Monika; et al. (SOAS Journal of Postgraduate Research, 2018)

The Gaze - Hirmer, Monika (Economic and Political Weekly, 2016)

‘The Role of Language in Diversifying Knowledge Production: Reflecting on the Experience of Decolonial Subversions as a Multilingual Publishing Platform’ - Hirmer, Monika; et al. (Decolonial Subversions, 2023)

The Self as Combination of Deities and Yantras: Divinisation Rituals among Contemporary Śrīvidyā Practitioners in India - Hirmer, Monika (Religions, 2022)
Divinisation rituals establishing oneness between practitioners and divinities are common across Tantric traditions. While scholars largely argue that divinisation occurs through meditative practices, implying a clear demarcation between contemplative samayācāra rituals and body-focused kaulācāra rituals, I suggest that samayācāra divinisation rituals entail fundamental corporeal elements; furthermore, I argue that the distinction between samayācāra and kaulācāra rituals is not obvious, but negotiated on a continuum ranging between representational and embodied corporeality. Based on extensive anthropological fieldwork in the temple-complex Śaktipur, I first illustrate divinised Śrīvidyā bodies: they are permeated by goddess Tripurasundarī in her anthropomorphic form and as a diagram, or yantra (the Śrīcakra), and by the deities Gaṇapati, Śyāmā, and Vārāhī, and their respective yantras. Thereafter, I describe yantrapūjās, which are samayācāra rituals through which practitioners divinise their bodies, outlining, particularly, their corporeal elements. I also illustrate sirījyotipūjā, which is a ritual directly transmitted by Tripurasundarī to Śaktipur’s guru and is, therefore, unique to his disciples. Foreseeing the creation of a large Śrīcakra decorated with flowers, around and at the centre of which practitioners congregate, the ritual facilitates the superimposition of the Śrīcakra, Tripurasundarī and worshippers’ bodies; including both representational and embodied elements, sirījyotipūjā occupies the fluid intersection between samayācāra and kaulācāra rituals.
Created from Fastlane, Scopus look-up
Keywords: anthropology; body; divinisation; Goddess traditions; ritual practice; South Asia; Tantra; yantra; Śrīvidyā